Dependence of aerosol-borne influenza A virus infectivity on relative humidity and aerosol composition - Motos, Ghislain; Schaub, Aline; David, Shannon C.; Costa, Laura; Terrettaz, Céline; Kaltsonoudis, Christos; Glas, Irina; Klein, Liviana K.; Bluvshtein, Nir; Luo, Beiping; Violaki, Kalliopi; Pohl, Marie O.; et al. (Frontiers in Microbiology, 2024)
We describe a novel biosafety aerosol chamber equipped with state-of-the-art instrumentation for bubble-bursting aerosol generation, size distribution measurement, and condensation-growth collection to minimize sampling artifacts when measuring virus infectivity in aerosol particles. Using this facility, we investigated the effect of relative humidity (RH) in very clean air without trace gases (except 400 ppm CO2) on the preservation of influenza A virus (IAV) infectivity in saline aerosol particles. We characterized infectivity in terms of 99%-inactivation time, t99, a metric we consider most relevant to airborne virus transmission. The viruses remained infectious for a long time, namely t99 > 5 h, if RH < 30% and the particles effloresced. Under intermediate conditions of humidity (40% < RH < 70%), the loss of infectivity was the most rapid (t99 ≈ 15-20 min, and up to t99 ≈ 35 min at 95% RH). This is more than an order of magnitude faster than suggested by many previous studies of aerosol-borne IAV, possibly due to the use of matrices containing organic molecules, such as proteins, with protective effects for the virus. We tested this hypothesis by adding sucrose to our aerosolization medium and, indeed, observed protection of IAV at intermediate RH (55%). Interestingly, the t99 of our measurements are also systematically lower than those in 1-μL droplet measurements of organic-free saline solutions, which cannot be explained by particle size effects alone.